Pickup and delivery supply chain network with semi soft time windows: metaheuristic approach. Issue 2 (3rd April 2017) - Setak, Mostafa; Azizi, Vahid; Karimi, Hossein; Jalili, Soheil
Abstract: This paper discusses a variant of supply chain networks including simultaneous pickup and delivery, and semi soft time windows. The emphasis of this research is on the soft time windows aspect of the problem. Semi soft time windows consider penalties on late arrival. However, waiting on early arrival is allowed without cost. The objective of the problem is simultaneously to locate the depots and to design the vehicle routes at a minimal cost, without violating pickup, delivery, or time windows constraints of the customers. We represent a mixed integer linear programming formulation for the problem. The solution to this problem is obtained through a CPLEX ® solver, a genetic algorithm, and a simulated annealing algorithm. Computational results are obtained on a set of randomly generated instances, and they indicate the efficiency of the proposed algorithms in terms of solution time and quality.